2016
DOI: 10.1021/acs.jafc.6b04346
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Antroquinonol and 4-Acetylantroquinonol B via a Polyketide Pathway Using Orsellinic Acid as a Ring Precursor in Antrodia cinnamomea

Abstract: Antroquinonol (AQ) and 4-acetylantroquinonol B (4-AAQB), isolated from the mycelium of Antrodia cinnamomea, have a similar chemical backbone to coenzyme Q (CoQ). Based on the postulation that biosynthesis of both AQ and 4-AAQB in A. cinnamomea starts from the polyketide pathway, we cultivated this fungus in a culture medium containing [U-C]oleic acid, and then we analyzed the crude extracts of the mycelium using UHPLC-MS. We found that AQ and 4-AAQB follow similar biosynthetic sequences as CoQ. Obvious [C] fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…In yeast and fungi, the benzoic ring of CoQ was from p ‐hydroxybenzoic acid . Biosynthesis of 4‐acetylantroquinonol B and antroquinonol was related to the CoQ pathway in A. camphorata …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In yeast and fungi, the benzoic ring of CoQ was from p ‐hydroxybenzoic acid . Biosynthesis of 4‐acetylantroquinonol B and antroquinonol was related to the CoQ pathway in A. camphorata …”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that CoQ 0 is considered an electron acceptor of the superoxide radical or a model for the quinone site in the bacterial photosynthetic reaction center . In A. camphorata , the carbocyclic core (CoQ 0 ) of antroquinonol could be synthesized via the polyketide pathway from malonyl‐CoA and acetyl‐CoA, and then sesquiterpene side chain and other chemical group were added by Coq2 – Coq6 genes . So, CoQ 0 is an efficient precursor for antroquinonol synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations